Why do we want health information? The goals associated with health information seeking (GAINS) questionnaire. Issue 3 (3rd March 2020) - Chasiotis, Anita; Wedderhoff, Oliver; Rosman, Tom; Mayer, Anne-Kathrin
Abstract: Objective: Individual goals of health information seeking have been widely neglected by previous research, let alone systematically assessed. The authors propose that these goals may be classified on two dimensions, namely coping focus (problem versus emotion oriented) and regulatory focus (promotion versus prevention oriented). Methods: Based on this classification, the authors developed the 16-item Goals Associated with Health Information Seeking (GAINS) questionnaire measuring the four goals 'understanding', 'action planning', 'hope' and 'reassurance' on four scales, and a superordinate general need for health information. Three studies were conducted to assess the psychometric properties of the questionnaire. Results: In the first two studies ( N = 150 and N = 283), internal consistency of the scales was acceptable to very good, and all items had a satisfying discriminatory power. Factorial validity was corroborated by an acceptable model fit in confirmatory factor analyses. In the third study, which included a patient sample ( N = 502), the questionnaire proved to be suitable for its target group and nomological relationships with personality as well as with situational variables providing evidence for construct validity. Conclusion: The GAINS is a reliable and valid assessment tool, which enables researchers and practitioners to identify an individual's goals related to health information seeking.